Genomic Sequence and Pathogenicity of the Chicken Anemia Virus Isolated From Chicken in Yunnan Province, China - Dai, Manman; Huang, Yuwen; Wang, Lin; Luo, Jing; Yan, Nan; Zhang, Lin; Huang, Haoqi; Zhou, Jie; Li, Ziwei; Xu, Chenggang (Frontiers in Veterinary Science, 2022)
Chicken anemia virus (CAV), which has been reported in many countries, causes severe anemia and immunosuppression in chickens. In this study, a CAV strain YN04 belonging to genotype A was firstly identified from infected chickens in Yunnan province, China. Moreover, the animal infection experiments further confirmed that the strain YN04 is a highly pathogenic strain, which can cause 86.67% mortality of chickens in infection group. The mean death time of infected chickens was 13.1 days post infection (dpi). CAV infection induced severe anemia with significant decrease of packed cell volume, and serious atrophy and lesion of thymus and bursa with high viral load at 14 dpi. Besides, CAV infection caused the sharp decrease of chicken body weight and immune organ indices including the ratio of thymus or bursa to body weight at 21 dpi, which displayed the potential immunosuppression state at this stage. These findings enrich the epidemiological data on CAV and may provide information for preventing its further spread in Yunnan province, China.